Mass Casualty in A Building Collapse: Techniques of Anaesthesia in Mass Casualty Management (Rana Plaza Collapse at Savar, Bangladesh) (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Background: Management of mass casualties in a disaster like situation needs much of discussion. Proper planning and preparation can markedly change the mortality and morbidity following these events. Similarly right use of special skill of anesthesiologists in the management of mass casualty is of immense value.Objectives: This study was aimed to investigate general injury profile, pattern of operations and anesthesia performed during mass casualty management of patients treated in the department of Anesthesia and Intensive care unit of Combined Military Hospitals, Savar.Methods: This study retrospectively investigated the clinical records of 155 patients files registered by many different doctors. We used discharge diagnosis, and when available objective x-ray or CT scan used for verification of fractures.Results: Among 431 patients reported to emergency and casualty department, 407 (94.431%) is admitted to hospital. Among 431 patients only 155 (35.962%) is treated in the department of Anesthesia and Intensive care. Among 155 patients of ICU, most of the injuries were blunt trauma soft tissue, rest of the injuries were fractures, head injuries, crush injuries etc, which accounts 95 (61.29%) patients. Majority of surgical procedure included wound debridment, fasciotomy, amputation and external fixation; constituted 51(33%) patients. 132(84%) surgical procedure performed under TIVA with ketamine, 22 (15%) under different regional techniques and only one patient received general anesthesia.Conclusion: Bangladesh is situated in a seismically active zone; fortunately no major earthquake has striken since 1940. Accelerated urbanization and high population densities in all cities are increasing the vulnerability of Bangladesh to catastrophic number of death and injuries. Ninety percent of casualties after earthquake result directly from the collapse of buildings in urban areas. The special skills of the anesthesiologist are of tremendous value in contributing mass casualty management in ICU and operating room. Our study concludes that surgical services can be maximized with the judicious and intelligent use of ketamine and regional anesthetic technique; rather than general anesthesia. Definitely it has strong value in maximizing use of scare resource in country like Bangladesh.Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 12-16